2007
DOI: 10.1097/01.ogx.0000253303.92229.59
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes: A Review of the Current Literature and Guidelines

Abstract: After completion of this article, the reader should be able to summarize that there is still no worldwide consensus on the diagnosis, management, and adverse effects of Gestational Diabetes Mellitus (GDM); explain that all methods of screening vary in sensitivity and depend on very strict preparations for screening; state that there is no agreement on ideal levels of blood glucose to prevent untoward effects; and recall that there are two very large prospective studies that clarify the dark waters and that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 76 publications
4
65
1
17
Order By: Relevance
“…14,15 This difference is even more exaggerated if GDM is untreated or when glycemic control is poor. 16 Although dystocia is a more common indication for cesarean delivery among GDM patients, 14 fetal distress is a more common indication among smokers.…”
Section: Discussionmentioning
confidence: 97%
“…14,15 This difference is even more exaggerated if GDM is untreated or when glycemic control is poor. 16 Although dystocia is a more common indication for cesarean delivery among GDM patients, 14 fetal distress is a more common indication among smokers.…”
Section: Discussionmentioning
confidence: 97%
“…The predictive value of maternal age in the development of GDM has been evaluated in several studies and the risk associated has been shown to be higher with increasing age (20,21,28,29). However, other authors have not reported a much higher risk for older women (22,30). A recent study examining the individual association of maternal age, BMI, and racial origin with the development of GDM has found different associated risks in relation to the prevalence of GDM for the specific racial group considered.…”
Section: Discussionmentioning
confidence: 98%
“…Relevancia cl铆nica de la investigaci贸n En el manejo de la diabetes mellitus gestacional con mal control metab贸lico en respuesta a la dieta: 驴es posible utilizar metformina en lugar de insulina para optimizar el control metab贸lico y mejorar el resultado perinatal? Escenario cl铆nico: La diabetes gestacional se presenta en una proporci贸n variable de las embarazadas, con un rango entre 3 y 10%, dependiendo de la poblaci贸n estudiada, el tipo de screening utilizado y el tipo de medio diagn贸stico (2). Si bien sus consecuencias son moderadas, la diabetes gestacional significa un mayor riesgo materno y perinatal, y un incremento en el riesgo de presentar diabetes mellitus tipo 2 en a帽os posteriores.…”
Section: An谩lisis De La Investigaci贸nunclassified